Peran Manajemen Perubahan Terhadap Kemajuan Organisasi - Mutiara Khinaya; Nuri Aslami (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Change is an unavoidable process in an organization. Organizational change is the process of moving from the present state to the future to improve the organization. An organization will always experience a change to anticipate and face challenges that will occur in the future. Organizational change can come from outside or from within the organization itself where the change is in the form of planned changes or structural changes that must be managed properly. Management in an organization is needed to help the change process so that the organization can improve its progress. The progress of the organization is very influential on the success or failure of an organization. Organizational change is not always well received because at every change there will inevitably be resistance. The existence of organizational change can be a threat of failure for an organization, therefore it is necessary to have good management so that an organization has progress.